Exploring the mechanical property and fire resistivity of sandwhich wall panel by utilizing polythylene terephthalate (PET) flakes and rope - Atega, Tim Andre' D.; Puso, Mark Ndsy L. (2020)
The rising usage of single-use plastics, which take hundreds and thousands of years to decompose, cause a huge accumulation of plastic waste in landfills and as a result, these cause serious environmental problems that affects not only the humans but also the animals. The study utilized PET Flakes as partial substitution for aggregates and PET Ropes as additional reinforcement for the sandwich wall panel. The aim of this study is to explore the mechanical properties and fire resistivity of the wall panel that - mainly focusing on the compressive, flexural and impact strength and fire rating and aimed to look into two physical property, density and specific weight. The study also aimed to compare the performance rating of the Polyethylene Terephthalate (PET) sandwich wall panel to the commercially available wall panels. Three mechanical tests were conducted, Compressive Strength Test, Flexural Strength Test and Impact Strength Test, to measure the maximum strength capacity of the sandwich wall panel with PET.The study tested the core layers of the sandwich wall panel and the sandwich panel with two different reinforcement spacing, 3 inches and 9 inches. There were nine formulations used in the study. The mortar mix used in the study is Class B; ratio of cement to aggregates is 1:3. The formulations differ in the percentage of PET and Sand of the 3 portions aggregates. Results showed that among the nine formulations, FR3 (1 portion cement and the 3 portions for aggregates is divided; 30% sand and 70% PET flakes and PET rope) with 3 inches reinforcement spacing -- with 2033.83 kg/m3 Density, 13.52Mpa Compressive Strength, 3069.40lb Flexural Strength (78 times its dead load), 5 times Impact rating and a 4 hour fire rating ? is the best formulation. With these results, FR3 sandwich wall panel can compete with the commercially available sandwich wall panels.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020